X-Ray Phase and IR Spectroscopic Investigation of Homogeneous and Mixed Ligand Complex Compounds of Calcium Acetate (Czech Journal of Multidisciplinary Innovations, 2023)
Homogeneous and mixed-ligand coordination compounds of calcium acetate with some amides have been synthesized. The composition, individuality, thermal behavior, methods of coordination of acetate groups and molecules of acetamide and nitrocarbamide have been established. The methods of coordination of organic ligands, the environment of the central ion, and the thermal behavior of the synthesized compounds have been proved by the methods of vibrational spectroscopy and thermal analysis. By comparing the interplanar distances and relative intensities of calcium acetate monohydrate and some amides, it is shown that the new coordination compounds differ from each other, as well as from the original components, therefore, the compounds have an individual crystal lattice.